2013
DOI: 10.1097/mjt.0b013e31827ab599
|View full text |Cite
|
Sign up to set email alerts
|

When Opioids Fail in Chronic Pain Management

Abstract: Clinicians are increasingly being challenged by patients who are treated for chronic pain with high-dose opioids that can cause medical, social, and societal harm. These patients may best be improved by psychological approaches, adjuvant medications, and opioid reduction or removal, rather than ever-escalating dosing that has become common. Opioid reduction or removal can be a difficult process that, when done incorrectly, may cause patient dissatisfaction or severe discomfort. Buprenorphine, a partial opioid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…[58] In addition, clinical studies, including a randomized clinical trial, have shown that substantial pain relief (66–82% pain reduction) can also be achieved in chronic pain patients who were placed on sublingual buprenorphine after failed other opioid therapies. [59, 60]…”
Section: Buprenorphine Alone In Pain Patients With Opioid Dependencementioning
confidence: 99%
“…[58] In addition, clinical studies, including a randomized clinical trial, have shown that substantial pain relief (66–82% pain reduction) can also be achieved in chronic pain patients who were placed on sublingual buprenorphine after failed other opioid therapies. [59, 60]…”
Section: Buprenorphine Alone In Pain Patients With Opioid Dependencementioning
confidence: 99%
“…Of the 128 articles, 22 qualified for inclusion in this study (Figure). These articles represented 5 RCTs (22.7%), 27,[35][36][37][38] 7 case-control or cohort studies (31.8%), 39-45 and 10 uncontrolled pre-post studies (45.5%), [46][47][48][49][50][51][52][53][54][55] which involved a total of 1642 unique participants (Table 1). However, Roux et al 36 randomized 51 participants but included only 25 in their analysis, decreasing the total number of participants to 1616 (675 female [41.8%] and 941 male [58.2%] individuals).…”
Section: Resultsmentioning
confidence: 99%
“…35,37,54 Individuals who were switching from methadone hydrochloride or transdermal fentanyl were instructed to wait longer (about 36-72 hours). 38,[47][48][49][50]54 In 2 protocols, participants were randomized to structured buprenorphine tapering conditions 35,56 ; in 1 study, participants were allowed to switch to the steady-dose group if they could not tolerate the tapering. 35 Another protocol required that patients were unable to taper their previous opioid use before being offered buprenorphine rotation.…”
Section: Rotation Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective study by Berland and colleagues studied patients with chronic pain experiencing worsening pain and function despite opioid use. 25 This study included patients on significant doses of opioids (median 400 mg oMED) and with multiple comorbidities. Following rotation to buprenorphine-naloxone, 67% of participants reported better pain control and 60% reported better function.…”
Section: High-dose Sublingual Buprenorphine For Chronic Painmentioning
confidence: 99%